Hubungan antara Brand Awareness dan Brand Quality dengan keinginan untuk kembali mengunjungi tempat wisata. Studi kasus pada Desa Wisata Cibuntu, Kuningan, Jawa Barat. - Supina - (Program Studi Hospitality dan Pariwisata, 2017)
Cibuntu is one of a village located in the area of West Java, which were just developing themselved in two years to be a tourist village. Within two years, the tourist village managed to show himself as one of the tourist village that should serve as an example, it is proved by various national publications and recognition from various Indonesian ministries, such as the Ministry of Environment This development does not occur only in Cibuntu, many other villages are also beginning to realize the positive multiplier effects generated by the tourism industry began to open up to become a tourist village. However, the concern of this phenomenon is there will be no differentiation between one village to another. Each village just look at the concept of the other villages that have a lot of visitors without any regard to the resources of their own. The question that arises is whether each of the tourist village know what actually makes tourists want to come back to visit the tourist village Therefore, researchers wanted to examine two dimensions of the brand equity that is on Brand Awareness and Brand Quality a tourist village if these two dimensions have a positive relationship with visitor's intention to re-visit a tourist village. Keywords : Brand Equity, Brand Awareness, Brand Image, Community Based Tourism